Appendicitis associated with a strangulated Littre's hernia - Jacob F. Quail; Romeo C. Ignacio (Elsevier, 2015)
A 12 year-old boy presented with right lower abdominal and groin pain. Intraoperatively, he was found to have acute appendicitis associated with a strangulated Meckel's diverticulum, or Littre's hernia. Both the appendix and Meckel's diverticulum were resected laparoscopically while the inguinal hernia was repaired four months later. We present an uncommon finding of a strangulated Littre's hernia discovered concurrently with acute appendicitis. The presentation, management and review of the literature of this condition are discussed.